Koncepcja nowego produktu w rachunku kosztów docelowych - Zackiewicz, Beata (Conception of New Product in Target Costing, 2007)
Effective management of the new product is today a key to success on very turbulent, not predictable market. Target Costing, one of the most appropriate tools for cost management of new product, is still not so popular in practice in Poland, and even more it is not enough known in marketing literature or by those authors who are interested in product management. Especially in Poland - only environment of accountants who are specializing in cost management - are fully conscious how important is TC. But still literature of Cost Management does not present exactly what should be understood by the concept of new product in Target Cost Management. The author of this article discusses a lot of different definitions of new product, presents same more popular classifications in marketing literature, and in the end, gives more appropriate definition of new product in Target Costing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 524-536